Integration of Toraja Local Wisdom into Contextual Chemistry Learning - Indah, Marwa; Erika, Farah; Usman, Usman (Chemistry Education Department of Education and Teaching Faculty, 2025)
This study explores traditional chemical practices within the Toraja community, an area of knowledge that remains underdocumented in existing scholarship. The research aims to: (1) describe chemical practices involved in the Rambu Solo’ funeral ceremony; (2) examine techniques for processing natural materials; and (3) discuss their pedagogical implications for chemistry education rooted in local wisdom. Using a qualitative ethnographic approach, the study was conducted in Tana Toraja and involved two purposively selected key informants: a teacher and a local cultural leader. Data were collected through in-depth interviews, direct observations, and documentation, then analyzed thematically. The analysis revealed two main themes. First, the use of pine leaves (Pinus merkusii) and tille wood in Rambu Solo’ functions as natural antiseptics and preservatives, a finding supported by literature on the bioactivity of terpenoids and phenolic compounds. Second, the fermentation of ballo’ and the production of natural dyes demonstrate biochemical processes and principles of green chemistry utilizing renewable natural resources. These findings show that Torajan traditional practices provide authentic and meaningful contexts for chemistry education. Incorporating such indigenous knowledge into the curriculum can make learning more relevant while helping preserve culture. Overall, this research offers an initial empirical basis for developing ethnoscience-based learning modules and suggests further studies involving quantitative chemical analyses and the development of innovative instructional materials. This approach can improve students’ scientific literacy and promote education for sustainable development.